An Error Analysis of Using Phrases in Writing Recount Text at Tenth Grade in SMA Parulian 2 Medan - Gadis Selvia Sitorus; Kammer Sipayung (Soegijapranata Catholic University, 2018)
This thesis is the study about an error analysis of using phrases in writing recount text at tenth grader in SMA Parulian 2 Medan. The objective of the study is to identify the types of common phrases’ error made by the students of tenth grader in SMA Parulian 2 Medan in writing recount text. This study used descriptive qualitative research. The subject of this study is the tenth grade students of SMA Parulian 2 Medan which consists of three classes. The object of this study is class of X-A. The instrument of collecting data used writing test, writing recount text. The data were analyzed by identifying the students’ phrases errors by underlining each error from students’ answer sheet, after that classifying the types of error based on five types of phrases. Finally, the research result showed that there are 145 phrases errors made by the students X-A in writing recount text. The types of phrases which indicate common error is on noun phrase. The number of noun phrase error are 83 with percentage 57,24%, followed by verb phrase has 28 with percentage 19,31%, the third is prepositional phrase which has 22 with percentage 15,17%, the fourth is adjective phrase which has 10 with percentage 6,90%, the last is adverb phrase has 2 with percentage 1,38%. It was caused the students constructed or arranged the words or sentences based on Indonesian meaning. English has different rules in constructing phrases. The students also were lack of knowledge about phrases. Therefore, English teachers are expected to focus on types of phrases in learning English.